2009
DOI: 10.3181/0902-rm-63
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of T-Cell Development in Adrenal Glucocorticoid-Deprived Rats

Abstract: A number of different experimental approaches have been used to elucidate the impact of basal levels of adrenal gland-derived glucocorticoids (GCs) on T cell development, and thereby T cell-mediated immune responses. However, the relevance of the adrenal GCs to T cell development is still far from clear. This study was undertaken to explore the relevance of basal levels of GCs to T cell differentiation/maturation. Eight days post-adrenalectomy in adult male rats the thymocyte yield, apoptotic and proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…Importantly, adrenalectomy induced thymic hyperplasia, as previously reported (compare Table 1 and Table 2, p<0.05, Ref. [29]). Results showed that adrenalectomized mice displayed a lack of response in the thymus to SU5416.…”
Section: Resultssupporting
confidence: 86%
“…Importantly, adrenalectomy induced thymic hyperplasia, as previously reported (compare Table 1 and Table 2, p<0.05, Ref. [29]). Results showed that adrenalectomized mice displayed a lack of response in the thymus to SU5416.…”
Section: Resultssupporting
confidence: 86%
“…Since the adrenaline level in adult rat thymus has been found to be below detection level (18), it may be assumed that the thymic changes in Adx rats mainly reflected a lack of adrenal GCs. This view is further supported by data showing that: i) noradrenergic nervous fibers represent the main source of CAs in the thymus (7,8), and ii) surgical stress does not affect any of the thymopoiesis parameters analyzed (12). The ineffectiveness of propranolol in enhancing thymocyte proliferation in the absence of adrenal GCs may be explained by the fact that thymocyte proliferation was measured in an unfractionated thymocyte suspension.…”
Section: Discussionsupporting
confidence: 61%
“…In conclusion, the present study pointed to GC-dependent plasticity of CA-mediated fine-tuning of thymopoiesis, and indirectly suggested that GCs influence T-cell development, not only by a direct action on thymocytes and thymic non-lymphoid cells (11,12), but also indirectly, affecting CA availability and/or AR sensitivity to CA signaling.…”
Section: Discussionmentioning
confidence: 98%
“…1 B ). Although ACTH seems to play an important role in thymocyte expansion at low GC concentrations, a role for GCs in this process may not be excluded because other reports have shown reduced apoptotic activity in the thymus following ADX (31, 32). However, at the time point we studied ADX effect on thymocyte homeostasis, we did not observe an altered basal apoptotic rate in wt mice (Supplemental Fig.…”
Section: Discussionmentioning
confidence: 99%